Community Pharmacists Assisting in Total Cardiovascular Health (CPATCH): A Cluster‐Randomized, Controlled Trial Testing a Focused Adherence Strategy Involving Community Pharmacies. Issue 10 (25th September 2016) - Blackburn, David F.; Evans, Charity D.; Eurich, Dean T.; Mansell, Kerry D.; Jorgenson, Derek J.; Taylor, Jeff G.; Semchuk, William M.; Shevchuk, Yvonne M.; Remillard, Alfred J.; Tran, David A.; Champagne, Anne P.
Abstract : Study Objective: To test a brief intervention for preventing statin nonadherence among community pharmacy patrons. Design: Prospective, cluster‐randomized, controlled trial (the Community Pharmacists Assisting in Total Cardiovascular Health [CPATCH] trial). Setting: Thirty community pharmacies in Saskatchewan, Canada. Patients: Participating pharmacies were randomized to 15 intervention pharmacies where a brief statin adherence intervention was delivered by pharmacists (intervention group [907 patients]) or 15 usual care pharmacies where no statin adherence intervention was delivered (usual care group [999 patients]) to new users of statins (defined as less than 1 yr of statin therapy). Intervention: Staff (pharmacy managers, staff pharmacists, and technicians) from intervention pharmacies attended a 2.5‐hour workshop on the CPATCH program that prepared pharmacists to deal with the adherence barriers most likely associated with statin use (e.g., safety, cost, patient–provider relationship, and tolerability). Intervention pharmacists screened for new statin users and assessed these adherence barriers. Pharmacists were then instructed to tailor their follow‐up plan based on the individual patient's situation. Investigators contacted the intervention pharmacies monthly to assess their compliance with the protocol and to offer additional support to motivate ongoing participation. Measurements and Main Results: The primary outcome was mean difference in statin adherence between the intervention and usual care groups. Adherence was measured by the proportion of days covered (PDC) between 6 and 12 months following the original prescription fill date. General estimating equations were used to evaluate the difference in mean adherence between groups. Secondary outcomes included the percentage of new statin users exhibiting optimal adherence (defined as PDC of 80% or higher) and the percentage exhibiting nonpersistence (defined as the cessation of all statin dispensations within 3 mo of the first dispensation). Among 1906 eligible patients, no significant differences in mean adherence were observed between those receiving the intervention and those receiving usual care (71.6% vs 70.9%, p=0.64), the percentage of patients achieving optimal adherence (57.3% vs 55.9%, p=0.51), or the percentage exhibiting nonpersistence (9.4% vs 8.3%, p=0.41). However, compliance to the study protocol was extremely low in several intervention pharmacies. In a post hoc analysis, a higher level of protocol compliance among intervention pharmacies was significantly associated with higher adherence (p<0.01 for trend). Pharmacies falling in the highest tertile of compliance to the study protocol exhibited higher mean adherence among their patients compared with those in the usual care group (β = 0.056, 95% confidence interval [CI] 0.010–0.101, p=0.01), and a significantly higher percentage of patients achieving optimal adherence (odds ratio 1.32, 95% CI 1.08–1.61; p<0.01); however, nonpersistence did not significantly differ between the two groups (5.5% vs 8.3%, p=0.27). Conclusion: The CPATCH intervention was ineffective for improving patient adherence to statin therapy in community pharmacies. However, poor effectiveness may have resulted from a failure to deliver the protocol consistently in several intervention pharmacies.